Negotiating Justice: An Islamic Legal Analysis of the Delay in Inheritance Distribution - Dasri, Dasri (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study aims to analyze the phenomenon of delayed inheritance distribution from a socio-Islamic legal perspective, focusing on the social, cultural, and religious dynamics that influence the practices of Muslim communities. Although Islamic law emphasizes the importance of distributing inheritance immediately after the decedent’s death, in reality, many families postpone the process due to concerns about maintaining harmony, moral readiness, and economic considerations. This research employs a qualitative approach using observation, interviews, and documentation to explore community and religious leaders’ views on the issue. The findings reveal that the delay in inheritance distribution is not merely caused by ignorance of Islamic law but also reflects social adaptation to customary norms and local authority structures. The study highlights that the implementation of Islamic law within society is not rigid but negotiated within dynamic social contexts. The socio-legal approach underscores that Islamic law functions not only as a normative system but also as an instrument of social consciousness capable of bridging the gap between legal texts and contemporary social realities. [Penelitian ini bertujuan menganalisis fenomena penundaan pembagian harta warisan dalam perspektif sosio-hukum Islam dengan fokus pada dinamika sosial, kultural, dan religius yang memengaruhi praktik masyarakat Muslim. Meskipun hukum Islam menegaskan pentingnya pembagian warisan segera setelah pewaris meninggal dunia, dalam kenyataan banyak keluarga menunda proses tersebut dengan alasan menjaga keharmonisan, ketidaksiapan moral, serta pertimbangan ekonomi. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi, wawancara, dan dokumentasi untuk menggali pandangan masyarakat dan tokoh agama terhadap praktik penundaan warisan. Hasil penelitian menunjukkan bahwa penundaan pembagian harta warisan bukan hanya akibat ketidakpahaman terhadap hukum Islam, tetapi juga merupakan bentuk adaptasi sosial terhadap norma adat dan struktur kekuasaan lokal. Temuan ini menegaskan bahwa penerapan hukum Islam di masyarakat tidak bersifat kaku, melainkan dinegosiasikan dalam konteks sosial yang dinamis. Pendekatan sosio-hukum memberikan pemahaman bahwa hukum Islam berfungsi tidak hanya sebagai norma normatif, tetapi juga sebagai instrumen pembentukan kesadaran sosial yang mampu menjembatani antara teks hukum dan realitas masyarakat kontemporer.]